1990
DOI: 10.1002/cjce.5450680114
|View full text |Cite
|
Sign up to set email alerts
|

High yield production of microcrystalline cellulose by a thermo‐mechano‐solvolytic treatment

Abstract: By thermally treating a commercial cellulose in ethylene glycol, celluloses of controlled low degree of polymerization, DPr = 1000 to 70, can be derived. Two general behaviors are observed in the range studied. At first, the depolymerization reaction is predominant down to a DP equal to 130. Beyond this level, the depolymerization process leads to extensive solubilization of the cellulose. The treated celluloses have been analyzed by X‐ray diffraction, FTIR, TGA, elemental analysis and enzymatic hydrolysis. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…All samples exhibited similar crystalline patterns. The widths at half height for the peaks at 2h = 17°and 26°are similar for all samples which suggests that their crystallite sizes are similar (Garnier et al 1990). In the case of the cotton gin waste MCC, an extra sharp peak was observed at 2h = 31°which was attributed to impurity quartz crystals in the sample.…”
Section: Enzyme Treated Corn Cob Microcrystalline Cellulosementioning
confidence: 79%
“…All samples exhibited similar crystalline patterns. The widths at half height for the peaks at 2h = 17°and 26°are similar for all samples which suggests that their crystallite sizes are similar (Garnier et al 1990). In the case of the cotton gin waste MCC, an extra sharp peak was observed at 2h = 31°which was attributed to impurity quartz crystals in the sample.…”
Section: Enzyme Treated Corn Cob Microcrystalline Cellulosementioning
confidence: 79%
“…T catalysed thermal organosolve treatment of lignocellulosics (Chornet et al, 1986) has been shown to solubilize lignin in high yield (Thring et al, 1989) and to produce a high purity cellulose (Bouchard et al, 1990). Despite the high temperatures used in this treatment the yield of cellulose is close the theoretical and the degree of polymerization (DP) can be maintained above 1200.…”
mentioning
confidence: 99%